Intercontinental analysis of temperate steppe stream food webs reveals consistent autochthonous support of fishes. (12th October 2022) - Arsenault, Emily R.; Thorp, James H.; Polito, Michael J.; Minder, Mario; Dodds, Walter K.; Tromboni, Flavia; Maasri, Alain; Pyron, Mark; Mendsaikhan, Bud; Otgonganbat, Amarbat; Altangerel, Solongo; Chandra, Sudeep; et al.
Abstract: Quantifying the trophic basis of production for freshwater metazoa at broad spatial scales is key to understanding ecosystem function and has been a research priority for decades. However, previous lotic food web studies have been limited by geographic coverage or methodological constraints. We used compound‐specific stable carbon isotope analysis of amino acids (AAs) to estimate basal resource contributions to fish consumers in streams spanning grassland, montane and semi‐arid ecoregions of the temperate steppe biome on two continents. Across a range of stream sizes and light regimes, we found consistent trophic importance of aquatic resources. Essential AAs of heterotrophic microbial origin generally provided secondary support for fishes, while terrestrial carbon did not seem to provide significant, direct support. These findings provide strong evidence for the dominant contribution of carbon to higher‐order consumers by aquatic autochthonous resources (primarily) and heterotrophic microbial communities (secondarily) in temperate steppe streams. Abstract : Quantifying the trophic basis of production for stream ecosystems has been a research priority for decades, but previous lotic food web studies have been limited by geographic coverage or methodological constraints. Using compound‐specific stable carbon isotope analysis of essential amino acids (EAAs), we found that aquatic, autochthonous resources (primarily) and heterotrophic microbes (secondarily) are responsible for producing the EAAs that support higher‐order fish consumers in temperate steppe streams.